Review on Smart in Situ Gels for Site Specific Delivery of Anti-Fungal: Opportunities and Challenges - Bala, Manisha; Dutta, Disha; Aslam, Ramsha; Bisht, Manoj (Journal of Neonatal Surgery, 2025)
Aims: The aim of this study is to explore the potential of in situ gel systems as innovative drug delivery vehicles, particularly for the treatment of invasive fungal infections (IFIs) in patients undergoing hematopoietic cell transplantation. The study emphasizes the advantages of in situ gelling systems in delivering antifungal agents locally or systemically with improved therapeutic efficacy and prolonged residence time. Methodology: The study involves the evaluation of in situ gel systems composed of synthetic, natural, or semi-synthetic polymers that exhibit a sol-to-gel transition in response to biological stimuli such as temperature, pH, or ionic strength. These gels can be formulated alone or in combination with mucoadhesive polymers to enhance site-specific drug retention. The potential of these gels as carriers for nanoparticles or microparticles is also considered. The clinical background includes the assessment of systemic Candida infections during the pre-engraftment phase in hematopoietic cell transplant patients and a comparison of the effectiveness of fluconazole, amphotericin B, and caspofungin as antifungal agents. Conclusion: In situ gel systems offer a promising strategy for the delivery of antifungal agents in immunocompromised patients, particularly those undergoing hematopoietic cell transplantation. Their stimuli-responsive behavior, prolonged residence time, and compatibility with nanoparticle carriers make them highly suitable for improving antifungal therapy. Integration with mucoadhesive polymers may further enhance therapeutic efficacy by increasing localization and bioavailability at the site of infection. Results: Systemic Candida infections were previously reported in 15–25% of cases during the pre-engraftment phase. The introduction of fluconazole prophylaxis has significantly reduced early infection rates. Caspofungin has emerged as a superior alternative due to its broad-spectrum activity and lower toxicity compared to amphotericin B. In situ gel systems have demonstrated the ability to respond to endogenous stimuli and effectively transition into gels post-injection, allowing for controlled and localized drug delivery